Effects of biodegradable mulching films on soil hydrothermal conditions and yield of drip-irrigated cotton (Gossypium hirsutum L.) - Wang, Dongwang; Wang, Zhenhua; Ding, Hongwei; Zhou, Bo; Zhang, Jinzhu; Li, Wenhao; Li, Haiqiang; Dhital, Yam P.; Wang, Tianyu; Zong, Rui (International Journal of Agricultural and Biological Engineering, 2022)
The pollution of cotton fields by residual films is serious on ground that has been subjected to long-term drip irrigation in Xinjiang, China, and biodegradable mulches are therefore advocated as an alternative to plastic ones. In this study the mulching with biodegradable films under drip irrigation conditions in the extremely arid region of Xinjiang was investigated to determine the effects on soil hydrothermal conditions and cotton (Gossypium hirsutum L.) yield over two consecutive years (2019–2020) using plastic mulch made from polyethylene (PE) film and four types of biodegradable films, including black opaque oxidation-biodegradable film (M1), colorless transparent oxidation-biodegradable film (M2), black opaque fully biodegradable film (M3) and white translucent fully biodegradable film (M4), which had different levels of biodegradability (i.e. different degradation times and rates). The biodegradability, soil water contents, soil temperatures and cotton yields were compared between the degradable (M1 to M4) and PE films. The results indicated that M2 was degraded the quickest and showed the highest degree of degradation compared with the other degradable films and PE films. The degradation rates of the various mulching films were ranked in a descending order as M2, M4, M1, M3 and PE, but the PE mulch exhibited the best performance in terms of soil water and heat conservation throughout the growth period. The soil heat preservation and moisture conservation performance under biodegradable films mulching at the cotton seedling stage and budding stage was similar to that of PE film. The average soil temperature at a depth of 5 cm under mulching with the degradable films was 2.66°C-5.06°C (p<0.05) lower than that under traditional PE films at the flowering stage. At the late stage of cotton growth, the water content of shallow soil mulched with PE film was better for plant grown than that under the biodegradable films. The effect of film degradation on the shallow soil water content was much greater than that in deep soil, especially at a depth of 0-40 cm. However, in all treatments, the seedling rate and growth index of cotton under M2 were equivalent to that found under the PE film. Moreover, the cotton yield using M2 was slightly higher than that those for the PE film. Compared with the PE film, the yield of cotton mulched with M1, M3 and M4 was decreased by 7.50%, 6.45% and 2.83%, and 9.82%, 6.48% and 2.13%, in 2019 and 2020, respectively. Therefore, based on the performance in improving cotton yield and maintaining soil moisture, the biodegradable transparent film (M2) with an 80 d induction period is recommended as a competitive alternative to plastic mulch to enhance crop yield and control soil pollution.Keywords: arid environment, biodegradable films, cotton yield, oasis agroecosystem, soil temperature, soil moistureDOI: 10.25165/j.ijabe.20221506.7353Citation: Wang D W, Wang Z H, Ding H W, Zhou B, Zhang J Z, Li W H, et al. Effects of biodegradable mulching films on soil hydrothermal conditions and yield of drip-irrigated cotton (Gossypium hirsutum L.). Int J Agric & Biol Eng, 2022; 15(6): 153–164.